Effect of Bacterial Isolates on Reduction of Physico Chemical Characteristics in Sugar Mill Effluent - Saranraj, P (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Bacterial Isolates on Reduction of Physico Chemical Characteristics in Sugar Mill Effluent